2000
DOI: 10.1093/molehr/6.5.429
|View full text |Cite
|
Sign up to set email alerts
|

Purification of GP-83, a glycoprotein secreted by the human epididymis and conjugated to mature spermatozoa

Abstract: Epididymal secretions are critical for mammalian spermatozoa to acquire both forward motility and an ability to recognize and penetrate oocytes. Previous studies identified two glycoproteins, GP-83 and GP-39, which were secreted by the human epididymis and may be related to maturation of sperm function. In this study, GP-83 was purified from human seminal fluid by DEAE-ion exchange, gel filtration chromatography and preparative gel elution. The isoelectric point (pI) of purified GP-83 was 6.57. Monospecific an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
0
13
0
2
Order By: Relevance
“…P34H (Legare et al 1999), and its counterparts in other species, such as P26h in the hamster , P31m in the monkey (Lamontagne et al 2001) and P25b in the bull (Frenette & Sullivan 2001), are proteins that enable sperm cells to properly bind to the zona pellucida of an oocyte. Similarly, the transmembrane protein 'a disintegrin and metalloproteinase 7 0 (ADAM7 or GP-83) is also transferred by epididymosomes to sperm cells, where it has been proposed to play a role in sperm-oocyte interaction (Sun et al 2000, Oh et al 2009). Besides membrane proteins, epididymosomes may also transfer cytosolic proteins, including aldose reductase and sorbitol dehydrogenase, both of which are enzymes of the polyol pathway; the former reduces glucose to sorbitol, while the latter oxidises sorbitol to fructose.…”
Section: Evs In the Male Reproductive Tractmentioning
confidence: 99%
“…P34H (Legare et al 1999), and its counterparts in other species, such as P26h in the hamster , P31m in the monkey (Lamontagne et al 2001) and P25b in the bull (Frenette & Sullivan 2001), are proteins that enable sperm cells to properly bind to the zona pellucida of an oocyte. Similarly, the transmembrane protein 'a disintegrin and metalloproteinase 7 0 (ADAM7 or GP-83) is also transferred by epididymosomes to sperm cells, where it has been proposed to play a role in sperm-oocyte interaction (Sun et al 2000, Oh et al 2009). Besides membrane proteins, epididymosomes may also transfer cytosolic proteins, including aldose reductase and sorbitol dehydrogenase, both of which are enzymes of the polyol pathway; the former reduces glucose to sorbitol, while the latter oxidises sorbitol to fructose.…”
Section: Evs In the Male Reproductive Tractmentioning
confidence: 99%
“…13,41 In both mice and humans, ADAM7 is synthesized in the epididymis, secreted, and transferred to mature sperm ( Figure 2). 13,70,71 During the epididymisto-sperm transfer process, ADAM7 in the epididymal lumen associates with membranous vesicles known as epididymosomes and the unprocessed protein relocates to sperm. 13,72 A recent study revealed that ADAM7 is associated with calnexin (CANX), heat shock protein 5 (HSPA5), and integral membrane protein 2B (ITM2B) in sperm membranes.…”
Section: Epididymismentioning
confidence: 99%
“…GP-83-expressing clones were identified by immunoscreening with GP-83-specific antiserum that was raised with purified GP-83 protein, and recognized a major molecule of 83 kDa in human epididymis and seminal fluid [19]. The inserts of the positive clones from the second subcloning were amplified by T3 primer and T7 primer in Taq polymerase system that revealed inserts of 0.7-2.1 kb.…”
Section: Cloning Of Gp-83-encoding Cdnamentioning
confidence: 99%
“…The proteins expressed in h-ADAM7-transformed competent E. coli BL21 (DE3) pLysS cells were examined on Western blots probed with GP-83-specific antiserum [19]. Among newly expressed proteins that reacted with His-specific antibody, GP-83 was identified by specific antibody (Fig.…”
Section: Identification Of Gp-83 Proteins Expressed By H-adam7mentioning
confidence: 99%
See 1 more Smart Citation